A three-way multi-attribute decision making method based on regret theory and its application to medical data in fuzzy environments - Zhu, Jinxing; Ma, Xueling; Zhan, Jianming; Yao, Yiyu (Applied soft computing, 2022)
Cardiovascular disease is a global leading cause of death, and timely monitoring can determine its extent. Clinicians use these diagnostic indicators to make scientific and reasonable decisions. However, when decision-makers (DMs) encounter risks in complex environments, their limited rationality may affect decision behaviors. Therefore, the paper explores a new three-way multi-attribute decision making method based on regret theory (3W-MADM-R), which uses heart disease data to make decisions in fuzzy environments. There are three main steps in developing 3W-MADM-R, i.e., (i) we propose the notion of relative outcome functions and corresponding aggregated regret-based utility functions of each object; (ii) we estimate the conditional probability via an outranked set defined by an outranking relation based on the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE II); (iii) we construct three-way decision rules to solve the problems of clustering and ranking of objects in data analysis. In order to demonstrate the usefulness of 3W-MADM-R, we apply it to analyze heart disease data. By comparing with results of other methods, we show the feasibility, stability and superiority of the presented 3W-MADM-R method. •A method to solve the problem for medical data is explored.•A new three-way multi-attribute decision making method based on regret theory is established.•Regret theory in behavior psychology is considered.•The feasibility, stability, and superiority of the proposed 3W-MADM-R method are verified.